WOOD TAR IN THE DNIEPER AND ELBE COMMUNITIES: VI – II MILLENIUM BC - Pietrzak, Sławomir (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2012)
The study ‘Wood Tars in the Dnieper and Elbe Communities: 6th – 2nd Millenium BC’ is the first European monograph of its kind in the professional literature devoted to the general question of the craft technology and application of wood tars among proto-agrarian communities across the long line of the Neolithic, Eneolithic and beginning of the Bronze Age across the vast expanse of borderlands joining Eastern and Western Europe. The research for the purpose of this monograph was undertaken at the University of Adam Mickiewicz in Poznań in partnership with the Institute of Prehistory and the Physico-Chemical Materials and Nanotechnology Section at the Faculty of Chemistry. The study was completed with the aid of chemical analyses of a comprehensive collection of wood tar samples documented in the course of excavations conducted in collaboration with a number of research-related institutions. The original work in Polish, ‘Zastosowanie i technologie wytwarzania dziegciu przez społeczeństwa międzyrzecza Dniepru i Łaby od VI do II tys BC’ [Wood Tar Crafts and Their Application Among Dnieper and Elbe Interfluvial Communities: 6th – 2nd millennium BC] was published in 2010 [‘Archaeologia Bimaris Monografie’, vol. 4] and received broad-ranging ‘interdisciplinary recognition’ from many scholarly circles in Central-Eastern Europe for the issues raised in respect to wood tars and their applications among prehistoric peoples. This consequently saw the decision to aim for a potentially broader readership through an abridged English version in the ‘Baltic-Pontic Studies’ series. The study was supervised in respect to on-going work and research methods by Professor Jerzy J. Langer at the University of Adam Mickiewicz, who also reviewed the monograph for publication.